PERLINDUNGAN HUKUM BAGI PEMBERI DAN PENERIMA LISENSI DALAM PERJANJIAN LISENSI HAK CIPTA ATAS PROGRAM SIARAN TELEVISI DI STASIUN TELEVISI TRANS7 - Anastasia, Mellinda (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2017)
In Doing Broadcasting, Trans7 Give Permission To Another broadcasting platform to broadcast its program and was also given permission by copyright holder to  broadcast its program. As mandated by the Copyright Act, those permits are made in the license agreement. Law No. 28 of 2014 on Copyright governing the license, which basically entitles the holder of copyright to grant a license to other parties via licensing agreements to implement or use a copyrighted work commercially by receiving royalties for the use of his creation. Licensor’s creativity is being protected in making a television broadcast program, and licensee’s right are protected to carry out broadcasting with the terms and conditions set forth in the license agreement. Licensor and licensee in the license agreement, including a license agreement the copyright to broadcast television programs on television stations TRANS7 which were not recorded in the Register of the General License Agreement Copyright remains protected of the rights held in the agreement, but the agreement was not have a legal effect to the third party.